Report of the Charity Organisation Committee on imbeciles, idiots, and harmless lunatics - SSISI (Statistical and Social Inquiry Society of Ireland, 1877)
We have considered the final report of the Special Committee of the Charity Organisation Society of London, on the ?Education and Cure of Idiots, Imbeciles, and Harmless Lunatics?, adopted on the 2nd of January in the present year, and we concur in the recommendations of the Committee. The Committee limit their recommendations to the extension to the rest of England and Wales of the plan attempted in the London Metropolitan District, but they add that they believe they are offering a model which will be accepted in principle far beyond these limits.
Read before the Society, 20 February 1877
Keywords: Charity Organisation Society of London; Intellectual disabilities; Special needs education; 314.15